Position Measurement And Control Of A Thin And Compact Linear Switched Reluctance Motor With A Disposable-Film Mover - Maslan, Mohd Nazmin; Sato, Kaiji; Shinshi, Tadahiko (Elsevier B.V., 2019)
This paper describes the position measurement and control of a thin and compact linear switched reluctance motor (LSRM) with a disposable-film mover.The paper proposes a position measurement method using the combination of the eddy current sensor output and a lookup table based on a previously measured information.The position measurement system based on the method is integrated into the developed LSRM to increase the disposability of the mover.The proposed method is robust to reproducible amplitude variation of the sensor output owing to the deformation of the mover.Experimental results showed that the measurement system can produce reliable position information,with a measurement error of up to 25 m and a resolution that is better than 10 m.Finally,the tracking performance of the control system using the measurement system as a feedback sensor is examined experimentally.